Clonal Forestry in India - Lal, Piare (Indian Forester, 2010)
Genetically improved clonal planting stock of Eucalypts, Poplars and Acacias has transformed the productivity and profitability of plantations. Average yields from such clonal plantations are 20 to 25 times higher compared to the average productivity of forests in India. Current levels of clonal Eucalyptus and poplar plantations produce nearly 5 million cubic meters wood valued at 21,000 million rupees annually. Plantations sustain most of the wood based pulp and paper mills and plywood/veneer factories in the country saving precious foreign exchange. Well managed clonal Eucalyptus plantations covering 1.25 million ha. can meet country's entire pulp and paper requirements projected at 8.5 million tonnes by 2010-11. Likewise, high yielding, short rotation clonal Eucalyptus plantations on part of the degraded forest lands can meet country's fuel-wood needs on sustainable basis. Clonal plantations, both on degraded forest lands and under agro-forestry system, should be encouraged and integrated with planned development of wood based industries through innovative policy changes.